The effectiveness of strategic planning in the management of sports riots - ALSHAMRANI, AHMED FAHAD (Journal of Risk and Crisis Management, 2019)
The present study aimed at reviewing some of the concepts (public awareness of the concept of sports intolerance and the riot of stadiums), to identify the role played by the audiovisual media (sports programs) and the sites of communication in igniting riots in Saudi stadiums, the review of security strategies for crisis management and sports disasters in the Kingdom of Saudi Arabia The protection of sports facilities - control of crowds and crowds - securing public and private property) from the point of view of the Saudi public and sports workers, to identify the awareness of the Saudi masses of the dangers of sports riots and their willingness to manage crises from During the course of the course, the researcher used the descriptive method and the analytical method. The sample was composed of a random sample consisting of a group of Saudi football fans and 106 male athletes in Jeddah. Most of the participants in the stadium riots are young people. The modern techniques used to monitor sports fields and the security system of the stadiums are very effective and contribute to reducing the risk of rioting in stadiums. , There is lack of transparency and clarity by some security agencies and there is no active participation of citizens with the regulatory system and regulators in a number of relevant sectors, whether security, sports or control, there is media awareness but not enough and need to improve, the most important recommendations: the imposition of control scenarios The introduction of sports programs that contribute to stir up anger, leading to riots in the stadiums, increase awareness programs and a spirit of satisfaction and rejection of intolerance and the idea of ​​blind imitation of some of the masses in some countries and adhere to our ethics and customs and the teachings of our religion.
Keywords: effectiveness; planning; strategy; sports riots